The Effect Of Performance Appraisal System On Employees Motivation: A Case Study Of Hospital A At Batu Pahat - Mohamad, Arifha; Mohamad zIN, Nurul Hafizah (Research in Management of Technology and Business, 2022)
The performance appraisal system is a critical aspect that may impact employees’ intrinsic and extrinsic motivation in the organisation. The purpose of this research is to identify the level of motivation at hospital A and examine the effect of the current performance appraisal system of Hospital A on staff motivation. Data will be collected by distributing a questionnaire survey to 150 employees of Hospital A randomly. The data was then analysed through a correlation coefficient.The expected outcome for this case study are there is relationship between performance appraisal and employee motivation. Furthermore, appropriate recommendations will be forwarded.